Dorsal posterior cingulate cortex encodes the informational value of feedback in human–computer interaction - Wolff, Susann (Sci Rep, 2020)
In communication between humans as well as in human–computer interaction, feedback is ubiquitous. It is essential for keeping up the dialogue between interaction partners, evaluating the adequacy of an action, or improving task performance. While the neuroscientific view on feedback has largely focused on its function as reward, more general definitions also emphasise its function as information about aspects of one’s task performance. Using fMRI in a computer-controlled auditory categorisation task, we studied the neural correlates of the informational value of computer-given feedback independent of reward. Feedback about the correctness of a decision, compared with feedback only indicating the registration of a decision, increases activation of the dorsal posterior cingulate cortex, supporting this region’s role in adapting to behaviourally relevant information. Both conditions elicit equally strong activation of the dorsal striatum which does not support an interpretation of feedback information as a type of reward. Instead, we suggest that it reflects a more fundamental aspect of human interaction behaviour, namely the establishment of a state that enables us to continue with the next step of the interaction.